(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
The article analyzes the concept of personality psychodiagnostics, its formation and role in psychological science. The main goals and objectives of personality psychodiagnostics, as well as its methodological significance in studying individual psychological characteristics, are examined. The relationship between personality psychodiagnostics and other branches of psychology is revealed, and its importance in practical psychological activities is substantiated. The article emphasizes the role of personality psychodiagnostics in education, clinical psychology, counseling, and social psychological practice.